The Rise, Fall, and Recovery of the Microfinance Sector in Morocco - Reille, Xavier (World Bank, Washington, DC, 2012)
Morocco is a recognized microcredit champion, boasting 40 percent of client outreach in the Arab world and host to some of the best performing microfinance institutions (MFIs) in the world. But since 2007, the microcredit sector has been confronting a crisis. There are 12 licensed MFIs in Morocco, serving close to 1 million clients with combined assets of 5.7 billion dirham (US$705 millio